ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), INFLASI (INF), NON PERFORMING LOAN (NPL),DAN DANA PIHAK KETIGA (DPK) TERHADAP PROFITABILITAS BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fendi Indra Laksana, 12.05.52.0018; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2017)
This study aims to examine the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Inflation (INF), Non Performing Loan (NPL), and Third Party Fund (DPK) to profitability in bank research was conducted using purposive sampling for sampling used and there are 69 companies were selected as sample. The analysis technique used in this research is multiple regression analysis using SPSS where previous data was tested using the classical assumption test.Keywords: Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Inflation (INF),Non Performing Loan (NPL), and Third Party Fund (DPK)